2015
DOI: 10.1002/ange.201502813
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Non‐Equivalence of Serine and Threonine O‐Glycosylation Points: Implications for Molecular Recognition of the Tn Antigen by an anti‐MUC1 Antibody

Abstract: The structural features of MUC1-like glycopeptides bearing the Tn antigen (a-O-GalNAc-Ser/Thr) in complex with an anti MUC-1 antibody are reported at atomic resolution. Fort he a-O-GalNAc-Ser derivative,t he glycosidic linkage adopts ah igh-energy conformation, barely populated in the free state.This unusual structure (also observed in an a-SGalNAc-Cys mimic) is stabilized by hydrogen bonds between the peptidic fragment and the sugar.T he selection of ap articular peptide structure by the antibody is thus prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…For α ‐linked Ser, ψ S can span almost all of 0° to 360° when φ S ≈60°; in Thr the additional methyl group splits the energy landscape at ψ S ≈240°. This difference between system 1 and 2 has an important implication in biological recognition, since antibodies exhibit different affinities towards glycopeptides having α ‐linked Ser or α ‐linked Thr . Our free‐energy landscapes can capture this difference with the lowest minima at φ S ≈60° while ψ S ≈60° and 120° for system 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…For α ‐linked Ser, ψ S can span almost all of 0° to 360° when φ S ≈60°; in Thr the additional methyl group splits the energy landscape at ψ S ≈240°. This difference between system 1 and 2 has an important implication in biological recognition, since antibodies exhibit different affinities towards glycopeptides having α ‐linked Ser or α ‐linked Thr . Our free‐energy landscapes can capture this difference with the lowest minima at φ S ≈60° while ψ S ≈60° and 120° for system 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…This difference between system 1 and 2 has an important implication in biological recognition, since antibodies exhibit different affinities towards glycopeptides having α-linked Ser or α-linked Thr. [67] Our free-energy landscapes can capture this difference with the lowest minima at ϕ S � 60°while ψ S � 60°and 120°for system 1 and 2, respectively. This was recently confirmed experimentally to be the main conformers in solution and in the bound state.…”
Section: Free-energy Landscapementioning
confidence: 91%
“…These observations led to the hypothesis that the antibody must specifically bind the carbohydrate as well as the peptide. X-ray crystallography of the structures of AR20.5 [ 24 ] and SM3 [ 133 ] in complex with both peptide and glycopeptide revealed that the carbohydrate did not have any specific polar contacts with the antibody. The high affinity for the glycopeptide and the lack of specific binding contacts of AR20.5 suggest that glycosylation of MUC1 stabilizes an extended bioactive conformation of the peptide that is recognized by the antibody.…”
Section: Molecular Interactions Between Muc1 and Its Antibodiesmentioning
confidence: 99%
“…The study pinpointed how the amino acid sequence and the sugar moiety are key factors modulating the binding to the antibodies 93. In 2015, Corzana and co-workers reported a detailed structural study regarding binding differences between α- O -GalNAc-Ser and -Thr MUC1-like glycopeptides 94. X-ray crystals with SM3, an anti-MUC1 antibody, revealed that the glycosidic linkage of the bound Tn-Ser antigen and the Tn-Thr analogue featured different conformations, which finally impacts on their binding affinities.…”
Section: Introductionmentioning
confidence: 99%